Issues of human potential development in the republics of the Russian Federation (according to the results of a survey of experts in Dagestan and Tuva) - Valiakhmetov, Rim M.; Zaripov, Ayrat Ya.; Turakayev Marсel S. (The New Research of Tuva, 2022)
The article deals with studying issues and features concerning the development of human potential in the national republics of the Russian Federation through the examples of Dagestan and Tuva. The presented observations and conclusions are based on the analysis of statistical data and expert assessments of representatives of both republics received in 2020–2021. It has been found out that the republics have similar features in their development, primarily in the economic, social and demographic spheres (a low level of economic development, a significant number of unemployed population, a high birth rate), and their own characteristics related to the ethnic specifics of their development (language, culture, religion, traditional economic activities, etc.). In the republics of Dagestan and Tuva, a certain attention is paid to the development of human potential, but it is insufficient. This is primarily due to the general economic situation in the country and the ins and outs of the development of the territories. Neither Dagestan nor Tuva has large modern production facilities. This fact negatively affects not only the economic development of these territories, but also their social sphere. There is an overabundance of labor force in the republics and it remains unclaimed in the economies of the regions. These factors are accompanied by a high birth rate and cause migration of the population to other regions. The development of private entrepreneurship is hindered by the imperfection of legislation, corruption and the shadow economy, paternalistic sentiments of the population, disbelief in social justice, etc. The current problems negatively affect the development and reproduction of the human potential of the republics in the following fields: education and personal development of the younger generations (insufficient number of preschool and educational institutions, overcrowding in children’s groups and classrooms, lack of teachers and educators); health care system (lack of medical personnel, polyclinics, hospitals, equipment); day-to-day leisure (lack of theaters and cinemas, cultural centers, libraries and sports facilities). There are also a lack of permanent and reliable Internet access in various regions of the republics. Experts associate the overcoming of existing problems in the development and realization of human potential with the implementation of reforms in the field of management and with a more consistent fight against localism and corruption.